Optical coherence tomography angiography for monitoring the treatment of neovascular age‐related macular degeneration - Fotis, Konstantinos (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows: To determine the diagnostic accuracy of OCT‐A (index test) compared to the combination of SD‐OCT and FFA (reference standard) for the monitoring of active CNVMs, to decide on the need for retreatment in people with nAMD who have already received antiangiogenic therapy. By definition an OCT‐A is the combination of SD‐OCT and OCT‐A, as a SD‐OCT scan is always produced by the OCT‐A machines at the time of the angiogram. Should OCT‐A prove to be as sensitive and specific as the combined use of SD‐OCT and FFA, it could replace the latter in daily clinical practice, since it is easier, faster and safer to perform. In current clinical practice FFA is not performed at every visit due to its inherent drawbacks. For the purpose of this review we will examine studies comparing OCT‐A to SD‐OCT alone or with FFA, in a multi modal imaging setting. As per clinical practice not all patients receive FFA, we therefore plan to conduct subgroup analyses for studies that always use FFA compared with studies that sometimes use FFA.